Aspectos conceptuales y metodológicos en estudios urbano-ambientales - Schteingart, Martha (El Colegio de México A.C., 2000)
This study comments on the methodological aspects implied in the creation of an interdisciplinary study on the urban environmental problem, coordinated by the author of the article. It begins with a review of the papers linked to the central theme of this study: Compliance with the law in the process of urban growth in areas of environmental interest in the Metropolitan Zone of Mexico City for which it uses contributions from the various fields of study involved in the theme (in other words, from the area of urban, legal and biological studies) . It goes on to analyze the principal difficulties involved in integrating the various types of knowledge required for the development of the central theme, highlighting the specific conceptual and methodological differences between the various disciplines within this context. The study also examines the principal obstacles involved in creating an interdisciplinary research team, and finally presents some of the results that have already been achieved or that are anticipated for future stages of the research as regards the understanding of the urban-environmental relationship and the interdisciplinary integration which this entails.